2002
DOI: 10.1128/aem.68.10.4820-4826.2002
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Transcriptional Analysis of the Chlorite Dismutase Gene of Dechloromonas agitata and Its Use as a Metabolic Probe

Abstract: Recent concerns over the environmental contamination of water supplies with perchlorate have focused a significant amount of attention on the microbial metabolism of oxyanions of chlorine (29). Perchlorate contamination poses a significant health threat, as preliminary toxicological studies have demonstrated that it is a competitive inhibitor of iodine uptake by the thyroid gland, and at higher concentrations (6 mg per kg of body weight per day), perchlorate can result in fatal bone marrow disease. In 1998, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…Phenotypic characterization studies have demonstrated that the known perchlorate-reducing bacteria exhibit a broad range of metabolic capabilities and can thrive in adverse environments (10; J. Pollock, L. A. Achenbach, and J. D. Coates, unpublished data). Significant advances have similarly been made in the biochemistry and genetic systems involved in microbial perchlorate reduction and on the environmental factors which affect their activity (5,6,8,10). As such, the applicability of this metabolism offers great potential for the bioremediation of perchlorate-contaminated environments, and recent field studies have successfully demonstrated this potential.…”
Section: Environmental Contamination With Perchlorate (Clomentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic characterization studies have demonstrated that the known perchlorate-reducing bacteria exhibit a broad range of metabolic capabilities and can thrive in adverse environments (10; J. Pollock, L. A. Achenbach, and J. D. Coates, unpublished data). Significant advances have similarly been made in the biochemistry and genetic systems involved in microbial perchlorate reduction and on the environmental factors which affect their activity (5,6,8,10). As such, the applicability of this metabolism offers great potential for the bioremediation of perchlorate-contaminated environments, and recent field studies have successfully demonstrated this potential.…”
Section: Environmental Contamination With Perchlorate (Clomentioning
confidence: 99%
“…Although several molecular and immunological tools based on unique signature molecules are now available to monitor the microbial populations associated with perchlorate reduction in the environment (5,6,24), monitoring of the effectiveness of a bioremediative strategy in field environments is often difficult due to the complex nature of environmental samples. Results can often be tainted by many abiotic factors, including adsorption or chemical reactivity of the target contaminant.…”
Section: Environmental Contamination With Perchlorate (Clomentioning
confidence: 99%
See 1 more Smart Citation
“…The dismutation of ClO 2 -into Cl -and O 2 , an important step in the reductive pathways of perchlorate, is mediated by an enzyme chlorite dismutase [15]. Degenerate primers were recently developed by Bender et al [16] for the amplification of the chlorite dismutase gene cld [17].…”
Section: Introductionmentioning
confidence: 99%
“…Work by Coates et al (1999), Chaudhuri et al (2002), and Bender et al (2002) indicate that the Dechloromonas and Dechlorosoma groups represent the primary chlorate and perchlorate reducing bacteria in the environment, but more than 30 different strains of perchlorate-reducing microbes have been identified (USEPA, 2005). The ratelimiting step in the three-step degradation process is the conversion of perchlorate to chlorate by a perchlorate reductase enzyme.…”
mentioning
confidence: 99%